PENGARUH E-WOM, ATMOSFER CAFE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA CILALULA COFFEE PAMULANG - Reisya Zahra Ardhika (2023)
This research is quantitative research which aims to determine, analyze and prove the influence of E-WOM, Atmosphere Cafe and Product Quality on Purchasing Decisions on Let us know Cilalula Coffee Pamulang. Cilalula Coffee is one of the industries that operates in the field Food and Beverage (F&B), namely a coffee shop business that provides a variety of food and drinks. Cilalula Coffee first active on social media, namely Facebook, on April 10 2019. Cilalula Coffee can maintain its business to date by maximizing factors, such as E-WOM, Atmosphere Cafe, and Product Quality which influence Purchasing Decisions. The population in this research are Cilalula Coffee customers who are active in South Tangerang. The sample size taken was 100 respondents using the method non-probability sampling with technique spurposive sampling. Data collection is carried out through distribution google form. The data analysis technique used is descriptive and inferential analysis with the SEM-PLS technique using the Smart PLS 4 application. The results of the research show that E-WOM positive and significant effect on Purchasing Decisions by 18.5%, Cafe atmosphere does not have a positive and significant effect on Purchasing Decisions by 13.2%,, and Product Quality has a positive and significant effect on Purchasing Decisions by 66.6%.